Applying ethical standards to guide shared decision-making with youth athletes - Michael McNamee (British Journal of Sports Medicine, 2018)
Despite the vast quantity of information available to patients, parents and clinicians, high-quality information and knowledge remains in relatively short supply.1 The benefits of an active lifestyle are incontrovertible. However, youth athletes have substantial risk for sports-related injuries to the musculoskeletal system and the brain.2 3 These potential dangers are known to clinicians who are helping youth athletes and their parents make sound decisions about injury management and sports participation. In the face of these challenges, how does the clinician fulfil his or her duty of care to youth athletes?The aim of this editorial is to illustrate how different ethical standards can help guide better shared decisions in sports medicine clinical practice. Youth athletes are a particularly vulnerable group because their life plans are still developing. Adding to this complexity is an increasing trend towards professionalisation in youth sport. When arriving at a decision in a clinical dilemma, one or several ethical standards may help the decision-making team evaluate if a decision is ethically justifiable. The 2018 International Olympic Committee consensus on paediatric ACL injury4 outlined six ethical standards (box 1) that may apply to different situations in sports medicine clinical practice.